Pengembangan Potensi Ekowisata Berbasis Kearifan Lokal di Kawasan Hutan Mangrove Tapak Kota Semarang - Yustina Denik Risyanti; Mengku Marhendi; Trenggono Trenggono; Phia Susanti Helyanan (Jurnal Visi Manajemen, 2025)
This research aims to develop the potential of ecotourism based on local wisdom in the mangrove forest area of Tapak, Semarang City. The methods used include field observation, interviews with local stakeholders, and qualitative data analysis. The results show that local wisdom plays an important role in managing the mangrove ecosystem and improving community welfare. Traditional practices applied by the local community are effective in maintaining environmental balance and addressing threats of abrasion and pollution. The Tapak mangrove area faces significant challenges, including coastal erosion and industrial waste pollution, which threaten the ecosystem's sustainability. However, the local community has developed various initiatives based on local wisdom for mitigation and conservation. Collective mangrove planting, the use of natural materials in pond management, and the implementation of zoning systems are some practices that have shown positive results. The development of ecotourism in this area not only has the potential to increase local income but also to strengthen environmental awareness among the community and visitors. Recommendations from this study include enhancing community capacity in ecotourism management, strengthening zoning systems, and promoting ecotourism based on local wisdom. Training and empowering the community in aspects of tourism guidance and sustainable resource management are key to ensuring the long-term success of this ecotourism. Therefore, sustainable and community-based ecotourism management strategies need to be continuously developed and supported by various parties to preserve the mangrove ecosystem and improve the welfare of the local community.